ANALYSISOF THE COMPOSITIONOFCATCHESOFFISHINGGEAR ATTHE TIMEOF UPSANDDOWNSINTHEBELITUNG BAYSUB-DISTRICTMERBAUDISTRICTMERANTIARCHIPELAGO - Santoso, Rian Nur Cahyo; H Bustari, H Bustari; Sari, T Ersti Yulika (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAC            One of the static fishing gear used by fishermen in Belitung Bay is a fishing gear. The purpose of this study is to know the composition of the catches in Teluk Belitung urban village. This research was conducted in October 2017 at Teluk Belitung Village, Merbau Sub-district, Meranti Islands Regency. The method used is the participatory method and the analysis used is t-test hypothesis analysis and chi-square test. From the results of this study obtained the total number of catches during the research is 78140 gr and 5538 tail. The dominant catch species during the study was red shrimp (Panaeus monodon) which was the main catch with weight 9660 gr and 1147 tails at the time of pairs, 10490 gr and 1242 tails at low tide. The t-test indicated that there was a difference in the number of catches at the time of tide and low tide and the chi-square test showed no difference in the composition of the catches at the time of tide and low tide.Keywords: Belitung Bay Sub-District, Pengerih, Composition Catch Result, Tides